A New Alkaloid from the Stem Bark of Holarrehena antidysenterica (Linn) Wall. - Mohammed Ali3, Humaira Farooqi4, Hamid Nawaz Khan3*, Parwaiz Akhtar1, Mahesh Prashad Sharma2 (Journal of Phytology, 2010)
New alkaloid was isolated from the stem bark of Holarrehena antidysenterica. The structures of the alkaloids were established as 3b dimethylamino-19b-5, 9 (H) dienine, on the basis of spectroscopic techniques and by chemical means. Key words: Holarrehena antidysenterica, Alkaloids, Spectroscopic techniques, 3b Dimethylamino-19b-5, 9 (H) Dienine <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Parwaiz Akhtar et al. A New Alkaloid from the Stem Bark of Holarrehena antidysenterica (Linn) Wall. J Phytol 2/3 (2010) 87-88.